TERMS AND TYPES OF ADDRESS - Zayniyeva, Umida (Журнал иностранных языков и лингвистики, 2021)
In social life, people use language as a medium to communicate it is their way to organize and maintain their relationship with others. It is important to bear in mind that the purpose of people in conducting communication will affect its forms. Moreover, every society has its own way in conducting communication, especially in the way its’ members address other people. Speaking about the address terms, sometimes people find it difficult to differentiate between greetings, summons, and address terms. This article discusses specific terms and types of treatment